2019
DOI: 10.1016/j.tmaid.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Stand-by antibiotics encourage unwarranted use of antibiotics for travelers’ diarrhea: A prospective study

Abstract: Carriage of stand-by antibiotics encouraged less cautious use of antibiotics. Recommendations involving prescription of antibiotics for all travelers require urgent revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Older travelers used antibiotics for loose stools (54.2%), mild TD (62.1%), and ILI (63.0%), contrary to published guidelines that discourage the use of antibiotics when a bacterial infection is unlikely. Overuse of standby antibiotic has been previously described: in a study by Vilkman et al, travelers carrying antibiotics used them at significantly higher rates for milder and moderate TD than noncarriers (38.0% vs 4.0%) [ 18 ]. Perhaps travelers, out of an abundance of caution, preemptively take antibiotics with mild symptoms for precautionary measures, and unknowingly are increasing their risk of antibiotic-related harm [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older travelers used antibiotics for loose stools (54.2%), mild TD (62.1%), and ILI (63.0%), contrary to published guidelines that discourage the use of antibiotics when a bacterial infection is unlikely. Overuse of standby antibiotic has been previously described: in a study by Vilkman et al, travelers carrying antibiotics used them at significantly higher rates for milder and moderate TD than noncarriers (38.0% vs 4.0%) [ 18 ]. Perhaps travelers, out of an abundance of caution, preemptively take antibiotics with mild symptoms for precautionary measures, and unknowingly are increasing their risk of antibiotic-related harm [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…International travelers are at increased risk of acquiring QNS enteric bacterial infections and importing them into the United States, which can lead to onward transmission and domestic outbreaks of infections that are difficult to treat [4, 16]. Empiric antimicrobial treatment of travelers’ diarrhea is rarely required, is more common when travelers carry antibiotics with them [21], and may exacerbate the problem of acquisition and importation of antibiotic-resistant infections [3, 22, 23]. Fluroquinolones can also precipitate serious adverse events, such as rupture of the Achilles tendon, fatal dysrhythmias, and C .…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians providing pretravel health consultation should also consider antimicrobial stewardship principles and be cautious about the prescription of broad-spectrum antimicrobials for empiric use by travelers. Recent analyses have shown that although the occurrence of travelers’ diarrhea cannot be controlled for, reducing the use of empiric antimicrobial treatment for travelers’ diarrhea may be useful for lowering the acquisition of travel-associated AMR bacteria [ 21 ▪ , 55 ▪▪ , 82 ].…”
Section: Areas In Need Of Further Investigationmentioning
confidence: 99%